Electric refractory materials - Kumashiro, Yukinobu, 1939- (Marcel Dekker, 2000)
An exploration of electric refractory materials. It covers developments of blue light-emitting diodes using GaN-based nitrides for laser and high-temperature and -frequency devices. It also introduces growth and evaluation standards of films and bulk crystals.